ARTIKEL REVIEW: POTENSI BUAH BIT (Beta vulgaris L.) SEBAGAI BAHAN PEWARNA ALAMI DALAM FORMULASI LIP TINT - Khairunnisa, Fenny; Hasibuan, Elmi Sariani; Ismirza, Ulfa (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: In recent years, the increasing demand for natural cosmetics has driven research into plant-based dyes as an alternative to synthetic materials. One promising source of natural dyes is beetroot (Beta vulgaris L.) which contains betacyanin pigment compounds. This review article aims to review various literatures related to the potential, benefits, and challenges of using beetroot as a natural dye in lip tint formulations. Based on a review of various studies, beetroot extracts show antioxidant activity, intense coloring, and are safe for the skin. However, constraints such as color stability to light and pH are still challenges in its application in the cosmetics industry.Keywords: Beta vulgaris L, betacyanin, beetroot, lip tint.